A review of durability test protocols of the proton exchange membrane fuel cells for vehicle. (15th August 2018) - Chen, Huicui; Song, Zhen; Zhao, Xin; Zhang, Tong; Pei, Pucheng; Liang, Chen
Highlights: Reviewed the PEMFC stack durability test protocols overall. The characteristics and applications of the test protocols have been analyzed. The conclusion is guidance for PEMFC stack durability test protocols designing. Abstract: The automotive operating protocols is a comprehensive expression of a country or a region's road, climatic environment and driving habits. It is the foundation of energy consumption, test method and limit method for automobile products. It has direct impact on R & D, production and government access management of enterprises. For fuel cells vehicles, the lifetime is one of the main factors restricting their commercialization. Furthermore, the lifetime evaluation methods and its standard specifications of vehicular proton exchange membrane fuel cell are the critical factors to its technological development, but there is no authoritative recognized life evaluation method and test protocols so far. A logical fuel cell durability test protocol is the fundamental for developing the fuel cell life evaluation methods. A review on the state-of-art in the world for fuel cell accelerated test protocols was given, the research circumstances of different universities and research institutions in China, America, the European Union, Japan and so on are analyzed and summarized in detail. Then the essential characteristics and applicable environments of a comprehensive and effective durability test protocol are summarized based on the analysis and demonstration of the existing durability test protocols in literature. The work in this paper focuses on the research of durability test protocols of the fuel cell stack for the first time. The final conclusion will provide theoretical basis for establishing fuel cell durability test specifications and proposing life evaluation methods, and make a contribution to the long life research of vehicular fuel cells.